EXCITATION CONDITIONS OF IRON FLUORESCENT LINES IN SOLAR FLARES - Bayazitov, U. Sh. (Одеські астрономічні публікації, 2017)
The conditions of the excitation of the fluorescent lines Fe l 4063, 4123 Å in the solar flares are discussed based on the previous work (Bayazitov U.Sh., Sakhibullin N.A., Pisma Astron. Zh., 1991, 17, 337). These conditions are not challenging the theoretical picture and the observational data for these objects.